Crustal thinning and extension in the northwestern continental margin of the South China Sea. (14th December 2015) - Zhu, Junjiang; Li, Jian; Sun, Zongxun; Li, Sanzhong
Abstract: Multichannel seismic data on the continental shelf have been used to image the rift‐related shallow structural units of the Pearl River Mouth Basin across the northwestern margin of the South China Sea. The Hainan Uplift, Zhu 3 Depression and Shenhu‐Ansha Uplift zones are bounded by normal faults or listric‐normal faults, which suggest lithospheric extension on the continental shelf. Graben structures 10–15 km wide are imaged on the Wanshan Uplift and Northern Fault Terrace from the reflection data. The thinned continental crust and anomaly rift‐related crust in the depression zone and the transitional crust indicated by the wide‐angle OBS velocity model dominate the crustal structure of the continental shelf in the continental margin of the South China Sea. The different total crustal stretching factors in different shallow structural units suggest that non‐uniform horizontal stretching controls the crustal thinning. The total crustal stretching factor is ca . 1.4–1.6 at the coast area, ca . 1.67–1.8 in the rift‐depression zone and ca . 1.7–1.75 in the transitional crustal domain. Pure‐shear crustal thinning controls the crustal extension in the rift‐depression zone. The high heat flow anomaly in the vicinity of the seismic lines and anomaly rift‐depression velocity structure suggest that the crustal thinning on the continental shelf of the South China Sea can be produced by lateral mantle flow within the hotter regional lithospheric background. Copyright © 2015 John Wiley & Sons, Ltd.